2018
DOI: 10.5603/ep.2018.0032
|View full text |Cite
|
Sign up to set email alerts
|

Hormony tarczycy i otyłość: znana, lecz słabo rozpoznana relacja

Abstract: Hormony tarczycy (thyroid hormones, TH) są zaangażowane w wiele różnych procesów biologicznych, wliczając rozwój układu nerwowego, regulację metabolizmu pośredniego oraz zużycie energii. Aktywnie uczestniczą w podstawowym zużyciu energii i termogenezie adaptacyjnej i z tego względu mogą mieć wpływ na masę ciała w przebiegu chorób tarczycy. Otyłość to niezakaźna, przewlekła, zapalna choroba metaboliczna, która implikuje dodatni bilans energetyczny. Tkanka tłuszczowa produkuje szereg hormonów i adipocytokin, tak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 59 publications
(119 reference statements)
0
13
0
Order By: Relevance
“…On the other hand, obesity may be a cause of elevated TSH levels ( 10 ). One plausible explanation is that adipose tissue secretes inflammatory cytokines into the general circulation, such as tumor necrosis factor (TNF-α) and interleukin (IL-1, IL-6) ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, obesity may be a cause of elevated TSH levels ( 10 ). One plausible explanation is that adipose tissue secretes inflammatory cytokines into the general circulation, such as tumor necrosis factor (TNF-α) and interleukin (IL-1, IL-6) ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid hormones are primarily involved in metabolism and energy expenditure of individuals ( 9 ). Evidence suggests that thyroid dysfunction predispose to obesity, or vice versa ( 10 ). Overweight and obese children tend to have higher TSH levels ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…As it is well known, TSH is secreted in response to feedback from circulating thyroid hormone, thyroid hormone regulates body weight balance and body fat mass after its activation from the T4 to the active form T3 (13). A higher TSH concentration may be the result of a lower thyroid function (14), which may lead to a lower basal metabolic rate and obesity (15). However, other studies found that thyroid function and obesity may affect each other, such that adipose tissue secretes leptin, which contributes to the alterations in the secretion of thyrotropin-releasing hormone (TRH) and affects the secretion of TSH (16).…”
Section: Discussionmentioning
confidence: 99%
“…They are involved in the regulation of reproduction, apoptosis, inflammation, blood pressure, atherogenesis, and fibrinolysis through impact on the proliferation and hyperplasic changes, particularly in the presence of obesity. Adipose cells express receptors for these factors and are able to respond to metabolic changes, mainly energy and glucose homeostasis [45][46][47].…”
Section: Hormonal Activity Of Adipose Tissuesmentioning
confidence: 99%